High fidelity computational characterization of the mechanical response of thermally aged polycarbonate - Zhang, Z; Zhang, L; Jasa, J; Li, W; Gazonas, G; Negahban, M (Institute of Physics, 2017)
A representative all-atom molecular dynamics (MD) system of polycarbonate (PC) is built and conditioned to capture and predict the behaviours of PC in response to a broad range of thermo-mechanical loadings for various thermal aging. The PC system is constructed to have a distribution of molecular weights comparable to a widely used commercial PC (LEXAN 9034), and thermally conditioned to produce models for aged and unaged PC. The MD responses of these models are evaluated through comparisons to existing experimental results carried out at much lower loading rates, but done over a broad range of temperatures and loading modes. These experiments include monotonic extension/compression/shear, unilaterally and bilaterally confined compression, and load-reversal during shear. It is shown that the MD simulations show both qualitative and quantitative similarity with the experimental response. The quantitative similarity is evaluated by comparing the dilatational response under bilaterally confined compression, the shear flow viscosity and the equivalent yield stress. The consistency of the in silico response to real laboratory experiments strongly suggests that the current PC models are physically and mechanically relevant and potentially can be used to investigate thermo-mechanical response to loading conditions that would not easily be possible. These MD models may provide valuable insight into the molecular sources of certain observations, and could possibly offer new perspectives on how to develop constitutive models that are based on better understanding the response of PC under complex loadings. To this latter end, the models are used to predict the response of PC to complex loading modes that would normally be difficult to do or that include characteristics that would be difficult to measure. These include the responses of unaged and aged PC to unilaterally confined extension/compression, cyclic uniaxial/shear loadings, and sawtooth extension/compression/shear.